The Effect of Financial Literacy on Consumptive Behavior: Self-Control as a Mediator: Pengaruh Literasi Keuangan Terhadap Perilaku Konsumtif: Pengendalian Diri sebagai Pemediasi - Marcella, Eka; Aini, Evanitha Kurrata; Fikri, Muhammad Ali; Katsir, Ahmad (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The situation faced by the younger generation today can affect their consumptive behavior. The level of literacy and self-control are some of the variables that can affect a person's consumptive behavior. How financial literacy can affect a person's consumptive behavior is the aim of this study. To obtain research data, students of the Faculty of Economics and Business from various universities in the Special Region of Yogyakarta were given questionnaires. Research shows that self-control has the ability to mediate the effects of financial literacy on consumptive behavior. Thus, it can be concluded that when one's students have high financial knowledge, they are better able to control their consumptive behavior.